THE ROOTS OF TRADITIONAL ISLAM IN MODERNIST MUSLIM WORKS: K.H. Aceng Zakaria and the Intellectual Tradition of Pesantren - Rohmana, Jajang A (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
One of characters of modernist Islam organization in Indonesia is the opposition to traditionalist Islam practices. Initially, the modernist Islam activist also learned in the traditional Islam culture before they turned around. This study focuses on the roots of the traditional Islam among the modernist Islam organization activists, Islamic Union (Persatuan Islam/PERSIS). The study object is the historical life of the PERSIS chairman, Aceng Zakaria and his magnum opus works, al-Muyassar fÃ® â€˜Ilm al-Naá¸¥w and al-HidÃ¢yah fÃ® MasÃ¢â€™il Fiqh Mutaâ€˜Ã¢riá¸ah. Through a socio-intellectual historical approach, the study shows that the Islamic intellectual tradition of the modernist activists is inseparable from the learning of traditional pesantren. Aceng Zakaria, as a PERSIS ulama, originally learned at the traditional pesantren in the mid-twentieth century. The roots of traditional Islamic science influences his intellectual career which was reflected in his works. Both books, Arabic grammar al-Muyassar and fiqh discourse al-HidÃ¢yah demonstrate his connectivity to the intellectual of traditional pesantren. However, Aceng Zakaria, as a modernist and reformist ulama, also modified his explanation systematically and practically. This shows that the genealogy of intellectual tradition of pesantren has an important position in supporting the development of reformist Islamic ideas in Indonesia.